Coherence on Undergraduate Thesis Abstract Written by English Language Students - Muhamat Meygi Sapriawan; Noor Eka Chandra; Raisa Fadilla (Universitas Teknokrat Indonesia, 2022)
Coherence is one of the important aspects in academic writing. It affects the reader’s understanding about a text. Particularly in education, academic writing becomes the requirement for undergraduate students to claim their graduation by writing a thesis. Thesis has some important parts, one of them is a thesis abstract which delivers a brief summary about the whole thesis. Therefore, the students need to write the thesis abstract coherently to provide positive first impression and build the reader interest toward the thesis. However, many of the students are not aware to this demand. Based on the issue, this study aimed to reveal the coherence on undergraduate thesis abstract written by English Language Education Study Program students of Lambung Mangkurat University. This study applied descriptive qualitative approach. There were four abstracts from higher grade theses and four abstracts from lower grade theses analysed in this study that were selected by using purposive sampling. The analysis of coherence in this study was conducted by content analysis method based on the topical subject progressions applied in the abstracts. This study found that the coherence in the four abstracts of higher grade theses was consistent and the coherence in the four abstracts of lower grade theses was varied by the finding of two from four abstracts had failed to reach coherence. Based on the findings, it was suggested for the students to improve and build awareness in writing a coherent abstract for their thesis as a academic writing product. Keywords: coherence, topical subject progression, undergraduate thesis abstract